Labor Informality and Market Segmentation in Senegal - Carlos Rodríguez-Castelán; Emmanuel Vazquez (Institute of Labor Economics (IZA), 2022)
Understanding the selection of workers into informality is a policy priority to design programs to increase formalization across Sub-Saharan Africa, where nine out of ten workers are informal. This paper estimates a model of self-selection with entry barriers into the formal sector to identify the extent of involuntary informality in Senegal, a representative country in terms of levels of informality in West Africa and with one of the most rigid labor markets in the world. The results show that the desire of being formal is greater for workers with formal education, married, and a lower proportion of children younger than age five living in the household. The individual's preference for the formal sector also grows with age at a decreasing rate. The results also show that labor informality is mainly a voluntary phenomenon, with 30 percent of informal workers being involuntarily displaced into the informal sector. The results are robust to different model specifications, definitions of labor informality, and heterogeneous groups of workers.
Keywords: J42; J46; N37; 330; labor informality; segmentation; labor markets; Senegal